The mind as a scientific object : between brain and culture - Erneling, Christina E., 1951-; Johnson, David Martel (OUP E-Books., 2005)
Are all cognitive sciences equal? The contributors of this book argue that the answer is no, because only neurophysiology and cultural psychology are suited to account for the mind's ontology. The papers collected here have been chosen to clarify these alternatives. In particular, because other books have emphasized the neuroscience alternative, this book highlights the cultural solution.